MEDIATING ROLE OF SOCIAL ISOLATION IN THE RELATIONSHIP OF PERSONALITY TRAITS AND BURNOUT (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2023)
This research is of great significance for  discovering if social isolation mediated the  relationship of personality and burnout. There  were 270 responses collected from the employees  working in service and manufacturing industries.  The findings of the study indicated that the social  isolation has an effect on burnout. Moreover  social isolation acts as a partial mediator between  burnout and personality traits.
Keywords: Pandemic; Personality Traits; ocial Isolation; Burnout